Reproductive performance and egg and larvae quality from first generation peruvian grunt Anisotremus scapularis (Tschudi, 1846): a comparative analysis with spawns from wild broodstock - Cota Mamani, Noemi; Carrera Santos, Lili Jannet; Castro-Fuentes, Angélica; Leon Dominguez, Oneill; Flores Ramos, Leenin; Ruiz Soto, Anthony; Lazo, Juan Pablo; Duncan, Neil (Frontiers in Marine Science, 2023)
Anisotremus scapularis is a marine fish distributed along the Peruvian coast that is commercially important in local markets. IMARPE started research on this species aimed to condition breeders and control reproduction in captivity and avoid dependence on wild broodstock. Therefore, the present study characterized and compared the reproductive performance, quality of eggs and larvae between a first generation domesticated broodstock (F1B) and a wild broodstock (WB). The F1B and WB broodstocks were conditioned in recirculation systems (RAS) to spawn naturally from August 2021 to August 2022. The following parameters were recorded for each spawn, the total number of eggs, percentages of viable eggs and fertilization, and hatching, and biochemical analyses on each spawn were performed. Progeny from each spawning were assessed for survival activity index (SAI), and at 20 days' post-hatch (DPH), the temperature tolerance index (TTI) was analyzed. WB had significantly higher (P<0.05) egg production, egg diameter, oil globule diameter, and SAI than those of F1B. However, the percentage of viable eggs and hatching showed significantly higher values (P<0.05) in F1B spawns. A low correlation (r<0.50) was observed between the evaluated reproductive parameters in A. scapularis broodstock; nevertheless, it was significant in some cases. No significant differences were observed in protein, lipid, carbohydrate, or ash content in eggs, but ash content in the 20 DPH larvae differed, with higher values in F1B. A principal component analysis (PCA), indicated a strong relationship between F1B broodstock eggs and fatty